2019
DOI: 10.1111/jan.13990
|View full text |Cite
|
Sign up to set email alerts
|

Exercise, fitness and musculoskeletal health of undergraduate nursing students: A cross‐sectional study

Abstract: Aims:To describe the exercise, physical fitness and musculoskeletal health of nursing students.Background: Nursing students are prone to musculoskeletal disorders restricting work ability. Physical fitness and leisure-time exercise may affect responses to workplace exposures and risk for work-related musculoskeletal disorders. Design:A cross-sectional study. Method:Between August 2013 and April 2015, a convenience sample of 111 nursing students performed submaximal exercise tests. Nursing work, exercise and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…The results of our research confirmed the fact that PE students demonstrated higher levels of physical fitness than the students of medicine-related courses. Pugh et al (2019) and Stephens, Cochran, Hall, & Olsen (2012) dealt with the assessment of physical fitness and performance among students of medicine-related courses from Australia and USA and concluded that their physical fitness is insufficient and its improvement may increase their readiness for future work.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our research confirmed the fact that PE students demonstrated higher levels of physical fitness than the students of medicine-related courses. Pugh et al (2019) and Stephens, Cochran, Hall, & Olsen (2012) dealt with the assessment of physical fitness and performance among students of medicine-related courses from Australia and USA and concluded that their physical fitness is insufficient and its improvement may increase their readiness for future work.…”
Section: Discussionmentioning
confidence: 99%
“…Questionnaires aimed at collecting the main biometric and demographic data from the participants were used by most of the articles analyzed. The Standardized Nordic Musculoskeletal Questionnaire, which aims to identify the workrelated pains reported by workers, was used by Åkesson et al (2012), Almhdawi et al (2017), Bazazan et al (2019), Dalager et al (2019), Heidari et al (2019), Pugh et al (2019), Svensson et al (2008) and Veiersted et al (2008). Finally, other authors used other questionnaires, such as the Work Organization Assessment Questionnaire -WOAQ (Oakman et al, 2014), the Siegrist's Effort Reward Imbalance Questionnaire -ERI (Uusitalo et al, 2011) and the Depression, Anxiety and Stress Scale Questionnaire.…”
Section: Methodologies For Estimating Physiological Workloadmentioning
confidence: 99%
“…Bazazan et al (2019), Dalager et al (2019), Greaves et al (2018), Uusitalo et al (2011) used scales related to the participants' emotion during their working hours to research workers' main feelings when performing tasks. Using workers' opinions in subjective scales of effort, Dalager et al (2019), Greaves et al (2018), Liu et al (2018), Oakman et al (2014) and Pugh et al (2019) measured the amount of workload demanded during tasks based on energy spent.…”
Section: Methodologies For Estimating Physiological Workloadmentioning
confidence: 99%
See 2 more Smart Citations